2020
DOI: 10.23797/9783529018619-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon dating bone and antler artefacts from Mesolithic Hohen Viecheln (Mecklenburg-Western Pomerania, Germany)

Abstract: Besonderer Dank gilt dem Vorstand des Zentrums für Baltische und Skandinavische Archäologie Schleswig, besonders dem Direktor, Claus von Carnap-Bornheim, und der Forschungsleiterin, Berit Valentin Eriksen, die die Veröffentlichung dieses Bandes durch die Bereitstellung der erforderlichen Mittel für den Druck der Arbeit maßgeblich unterstützten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…According to Miller et al (1986), the wooden bow is the simplest and oldest solution to transfer the potential energy of a drawn bow to the arrow shaft; wood is also a legitimate material for arrow shafts and even arrowheads, as wood-tipped arrows were determined experimentally to behave similarly to stone-tipped arrows, with only 10% less penetration (Waguespack et al, 2009). Actual examples have been verified from the Upper Palaeolithic period onwards: fragments of a potential bow made of pine-wood (Pinus sylvestris) at Mannheim (Germany) dated at approximately 17,500-18,000 cal BP (Rosendahl et al, 2006) and a wooden arrow shaft from Stellmoor (Germany) dated to 11,970-11,260 cal BP (Meadows et al, 2018). A growing body of archaeological evidence gathered has confirmed that wood has importantly figured in the making of bows and arrows (e.g.…”
Section: Introductionmentioning
confidence: 91%
“…According to Miller et al (1986), the wooden bow is the simplest and oldest solution to transfer the potential energy of a drawn bow to the arrow shaft; wood is also a legitimate material for arrow shafts and even arrowheads, as wood-tipped arrows were determined experimentally to behave similarly to stone-tipped arrows, with only 10% less penetration (Waguespack et al, 2009). Actual examples have been verified from the Upper Palaeolithic period onwards: fragments of a potential bow made of pine-wood (Pinus sylvestris) at Mannheim (Germany) dated at approximately 17,500-18,000 cal BP (Rosendahl et al, 2006) and a wooden arrow shaft from Stellmoor (Germany) dated to 11,970-11,260 cal BP (Meadows et al, 2018). A growing body of archaeological evidence gathered has confirmed that wood has importantly figured in the making of bows and arrows (e.g.…”
Section: Introductionmentioning
confidence: 91%
“…Van Klinken and Hedges (1995) observed that humic substance uptake by collagen can be quick (several hours), and only ninhydrin and HPLC treatments could remove the humic contamination in the case of cross-linking. Meadows et al (2019) looked at Mesolithic bone and antler objects, which were consolidated with unknown material. Two types of consolidant with distinct FTIR-ATR peaks were used, one of which showed peaks that suggested cellulose nitrate, while the other consolidant could not be extracted and analyzed separately.…”
Section: Identifying Contamination Using Ftir-atrmentioning
confidence: 99%
“…However, discoveries of wooden tools have revolutionised our perspectives on Palaeolithic technologies and hominin behaviours. Noteworthy discoveries include wooden spears and digging sticks that together altered perspectives on Middle Pleistocene hominin diets and hunting [1][2][3], Late Glacial wooden arrows proving bow-and-arrow hunting during the Palaeolithic [4,5] and the Late Glacial Shigir idol, which is the earliest monumental sculpture [6]. In spite of the significance of such objects, and perhaps due to their rarity, methods to analyse wooden finds that do survive are underdeveloped, and particularly so in relation to processes of manufacture and use.…”
Section: Introductionmentioning
confidence: 99%